Roles and social adaptability of Bangladeshi migrant workers in commercialised farming of Cameron Highlands, Malaysia - Karim, A.H.M Zehadul; Rokis, Rohaiza; Basir, Norasikin (European Journals Inc., 2017)
This paper studies the roles and social adaptability of Bangladeshi plantation workers in Cameron Highlands, Malaysia who are involved in the newly-devised commercialised agricultural farming. Cameron Highlands has recently been identified as a strategic farming area for which many foreign workers including the Bangladeshis have been attracted to perform multifarious activities relating to plantation agriculture. Due to having profound socio-cultural background and proper farming orientation in their country of origin, these Bangladeshi workers are performing positively in the activities at various plantations. The findings of this research indicate that the Bangladeshi migrant workers in particular are adopting some special mechanisms for potential farming in Cameron Highlands but in terms of social adaptability, these workers are facing some challenges in relation to their socio-cultural interaction and living. The identification of these problems relating to foreign workers and understanding their intricate role and activities will allow policy planners to take note of future strategies in regard to protecting the labour sector of this economy.